1993
DOI: 10.1111/j.1365-2044.1993.tb07419.x
|View full text |Cite
|
Sign up to set email alerts
|

Addition of droperidol to patient‐controlled analgesia: effect on nausea and vomiting

Abstract: SummaryA double-blind trial of the effect of droperidol on the incidence of nausea and vomiting in patients using patient-controlled analgesia was carried out in 60 healthy women undergoing abdominal hysterectomy. After a standard anaesthetic including droperidol 2.5 mg as a prophylactic antiemetic, patients were randomly allocated to receive postoperative patient-controlled analgesia with either morphine alone ( 2 mg.ml-') or morphine ( 2 mg.rn1-') with droperidol (0.2 mg.ml-')

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(31 citation statements)
references
References 11 publications
3
28
0
Order By: Relevance
“…The VAS has been validated for assessment of nausea in antiemetic trials of oncology patients receiving chemotherapy, 24 and adopted for use in the postoperative setting. 9 Williams et al used a VAS to assess severity of nausea with PCA droperidol and found similar results to the present study with mean scores less than 2 out of 10 in both groups. 9 Despite the small range of scores documented by both of these studies, statistically significant reductions in severity were identified with the addition of droperidol to PCA morphine.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The VAS has been validated for assessment of nausea in antiemetic trials of oncology patients receiving chemotherapy, 24 and adopted for use in the postoperative setting. 9 Williams et al used a VAS to assess severity of nausea with PCA droperidol and found similar results to the present study with mean scores less than 2 out of 10 in both groups. 9 Despite the small range of scores documented by both of these studies, statistically significant reductions in severity were identified with the addition of droperidol to PCA morphine.…”
Section: Discussionsupporting
confidence: 79%
“…The population that we studied would appear to be an accurate sample as the placebo group had a 71% incidence of vomiting which is similar to that previously documented in women undergoing gynaecological surgery. 3 '4 In a similar population to the present study, Williams et al 9 found a reduction in the incidence of nausea at 12 hr and a reduction in its severity at both 12 and 24 hr when droperidol 0.10 mg.mg -~ PCA morphine was used after a bolus of 2.5 mg at the time of induction. Sharma et al ~~ used lower doses and demonstrated a 50% overall reduction in the incidence of nausea over 24 hr, while Barrow et al H established a reduction in the number of four-hourly assessments during which nausea occurred.…”
Section: Discussionsupporting
confidence: 50%
“…Khail et al [24] found droperidol (0.075 mg/kg) effective in PONV prophylaxis during strabismus surgery in children. Williams et al [25] applied patient-controlled analgesia with morphine in patients who had abdominal hysterectomies and in the treatment of postoperative pain; they reported that droperidol was effective in preventing PONV. Gan et al [14] found droperidol and patient-controlled analgesia effective in preventing PONV after orthopedic surgery; these results were similar to those found after gynecologic operations [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…However, Silverman et al [42] found the inclusion of promethazine with morphine PCA reduced nausea although the findings were dependent on the nausea scale used. Studies have found that the addition of droperidol (0.05-0.2 mg.ml ÿ 1 ) to morphine PCA has reduced the incidence of nausea and vomiting and, in some cases, the need for additional intramuscular anti-emetics [5,9,40,43,44]. However, some studies reported an increase in sedation associated with the use of droperidol [5,9,44] and Gan et al [45] argued that adding droperidol to PCA increases sedation with no benefit over a single dose of droperidol at the end of surgery.…”
Section: Giving Prophylactic Anti-emeticsmentioning
confidence: 99%
“…Studies have found that the addition of droperidol (0.05-0.2 mg.ml ÿ 1 ) to morphine PCA has reduced the incidence of nausea and vomiting and, in some cases, the need for additional intramuscular anti-emetics [5,9,40,43,44]. However, some studies reported an increase in sedation associated with the use of droperidol [5,9,44] and Gan et al [45] argued that adding droperidol to PCA increases sedation with no benefit over a single dose of droperidol at the end of surgery. Moreover, although extrapyramidal side-effects were not reported in any of the studies, they should be considered, particularly if PCA is to continue beyond 24 h. Collum et al [46] report a case study of a patient experiencing a dystonic reaction Ϸ30 h after surgery and while receiving PCA morphine with droperidol 0.2 mg.ml ÿ 1 added.…”
Section: Giving Prophylactic Anti-emeticsmentioning
confidence: 99%